Overview on the Utilization of Quarry Dust as a Replacement Material in Construction Industry - Abdul Hamid, Nur Jannah; Abdul Kadir, Aeslina; Mohd Kamil, Nor Amani Filzah; Hassan, Mohd Ikhmal Haqeem (International Journal of Integrated Engineering, 2018)
In line with economic development of the country, demand of raw materials for the construction, building and manufacturing sectors are also increasing. Concrete is a great significance that contributes to every construction practices. Concrete is the most widely used construction material in the world because of its ability to get cast in any form and shape. The strength and durability of concrete can be changed by utilizing suitable improvements in its ingredients such as cementitious material, aggregates and water. One of the raw materials used to produce conventional concrete is river sand which has significantly become very costly and becoming scarce due to river bed depletion therefore alternative material is in need. On the other hand, the growth of human population has led to concerns in solid waste management prior to major environmental problems that arose due to urbanization and industrial activities thus lead to its utilization in building material. There are different types of waste materials being used in the construction industry such as stone quarry dust, fly ash, rice husk, clay brick, metakaolins, palm oil fuel ash, bamboo leaf ash, volcanic ash, ground nut husk ash, waste glass, slurry glass powder, quarry dust and marble dust powder. Nevertheless, this paper only reviews on quarry dust as sand replacement in construction industry.